A Hybrid Ring‐Opening Metathesis Polymerization Catalyst Based on an Engineered Variant of the β‐Barrel Protein FhuA. Issue 41 (19th August 2013) - Philippart, Freddi; Arlt, Marcus; Gotzen, Steve; Tenne, Stefanie‐Joana; Bocola, Marco; Chen, Hsui‐Hui; Zhu, Leilei; Schwaneberg, Ulrich; Okuda, Jun
Abstract A β‐barrel protein hybrid catalyst was prepared by covalently anchoring a Grubbs–Hoveyda type olefin metathesis catalyst at a single accessible cysteine amino acid in the barrel interior of a variant of β‐barrel transmembrane protein ferric hydroxamate uptake protein component A (FhuA). Activity of this hybrid catalyst type was demonstrated by ring‐opening metathesis polymerization of a 7‐oxanorbornene derivative in aqueous solution.